Optimalisasi Bhabinkamtibmas Guna Mengurangi Penyalahgunaan Narkotika Di Kalangan Pelajar Di Wilayah Hukum Polres Kuningan - Bayu Dhamma Roosdirgo (Indonesian Journal of Police Studies, 2020)
Misuse and illicit trafficking of narcotics is a form of real danger that must be dealt with seriously, and continuously by involving all elements of the nation. One concrete manifestation of efforts to eradicate the abuse and illicit trafficking of narcotics is the enactment of Law No. 35. 2009 concerning Narcotics on September 14, 2009. The law is a refinement of Law No. 22 of 1997 concerning Narcotics and Law No. 5 of 1997 about Psychotropics. The National Police of the Republic of Indonesia as a state tool in the function of maintaining security and public order must be able to realize the desire of the people to be free from the abuse and illicit trafficking of narcotics. In this case, in accordance with the main tasks of the National Police listed in article 13 Chapter III of Law No. 2 of 2002 concerning the Indonesian National Police, the main tasks of the Indonesian National Police are; maintain public security and order, enforce the law, and provide protection, protection and service to the community. The public demand for the National Police to eradicate narcotics abuse and illicit trafficking has increased, because the public has now realized that the negative effects caused by narcotics abuse and illicit trafficking are so large and dangerous. The general public only knows that narcotics are prohibited, that narcotics are difficult to obtain. In fact, narcotics can be in any form and is very easy to get in public. Therefore, our role as members of the National Police is urgently needed to socialize the impacts caused and the losses that will be obtained when dealing with drugs.